Comparison of body image and peer relations among girls with normal, early, and late menarche - Elham Irannezhad; Maryam Fooladvand; Mohammad Soltanizadeh (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The onset of menstruation is a turning point in women's sexual maturity that, unlike other stages of growth, occurs abruptly and is a critical stage in girls' lives. The present study investigated body image and peer relations among girls with early, late, and normal menarche. MATERIALS AND METHODS: This casual-comparative descriptive study included female students aged 9-17 in Isfahan. The participants were selected using multistage cluster random sampling. Out of 5,984 students, 56, 37, and 43 were selected for the normal, early, and late menarche groups. The Body Image Concern Inventory and Index of Peer Relations were the two tools used in this study. Moreover, the data were analyzed using a covariance statistical test. RESULTS: Girls with early menarche had better peer relations than those with late menarche (P = 0.01). In addition, there was a significant difference between adolescents with normal and late menarche in terms of body image (P = 0.01). Girls who experienced late menarche were more concerned about their body image and appearance; however, girls with early menarche experienced more impaired performance (P = 0.05). CONCLUSION: The first menstrual cycle, or menarche, affects psychological variables such as body image and peer relations. The later the menarche, the fewer problems in regard to body image and peer relations.